Gambaran Deskriptif Produk Banana Roll Sebagai Camilan Sehat Masa Kini (Description of Banana Roll Product as a Healthy Snack) - Danisa Alifa Salsabila; Dini Khairunnisa; Milliyantri Elvandari; Muhammad Akhdiyatul Aein (Program Studi Gizi UNSIKA, 2021)
Banana Roll is an entrepreneurial product made as a healthy snack today. Banana Roll (pisgul) is a product made from processed bananas wrapped with spring roll skin and topped with toppings. This product is made from bananas that are ripe enough to have a sweet taste. The purpose of making Banana Roll is as a snack or healthy snack that has high nutritional value, and to use bananas as a food ingredient that is quite popular with people of all ages, from children to the elderly. Keywords: banana, banana roll, entrepreneurship